KOMUNIKASI PEMBANGUNAN, PARTISIPASI MASYARAKAT DAN MEDIA ONLINE PADA PROGRAM BERBAGI AIR DI DESA PASAREAN KABUPATEN BOGOR - Sutowo, Irpan Ripa'i; Wahyuningratna, Ratu Nadya (Pusat Penelitian dan Pengabdian Masyarakat, Politeknik Negeri Batam, 2020)
This study discusses the problem of access related to clean water and sanitation in rural settlements that do not have clean water and sanitation facilities to meet their daily needs in Pasarean Village, Pamijahan District, Bogor Regency. Citizens' efforts in dealing with problems are also described in this study. The background and problems of this research are the lack of access to clean water and sanitation in rural areas due to geographical factors, such as the position of being in the hills, into clean water, and the distance to access to get distant water. So the clean water sharing program in the form of well drilling was carried out to solve the problem, which was assisted by PKPU donors from humanitarian agencies. The purpose of this study is to determine the level of participatory development communication in water sharing programs. This research method is a qualitative descriptive method with data collection techniques, namely participatory observation. The results of this study indicate that development communication runs in a participatory manner, whereby the community participates actively in every process of building clean water facilities starting from planning to utilizing development programs. The level of community participatory development communication can be seen at the level of community participation, where community participation is at the level of acting together, which means that in achieving the goal of meeting the needs of clean water facilities the community does not merely participate in making decisions, but also engages and establish partnerships in the implementation of the program.